Optimasi Penjadwalan Tenaga Kesehatan di Puskesmas Teja Kabupaten Pamekasan Menggunakan Solver Excel - Defilia Fatikasari; Yoga Septian Dwi Pratama; Hozairi (JOKI: Jurnal Komputasi dan Informatika, 2024)
The Teja Community Health Center, Pamekasan Regency is experiencing problems in managing the scheduling of health workers (Doctors, Nurses and Midwives) optimally, which can result in an imbalance in workload and high idle time (periods of not serving patients). This research aims to optimize the scheduling of health workers at the Teja Community Health Center using Solver Excel. This research uses quantitative methods with a descriptive analytical approach, with data on the number of health workers and maximum working hours collected and analyzed. A linear scheduling model was created using Solver Excel to minimize idle time for health workers. The research results show that optimal scheduling with appropriate assignments on admission and non-admission days, as well as an even distribution of workload can increase operational efficiency and reduce idle time, thereby increasing the efficiency of using health workers. The research results also include information about the number of 2 doctors, with a total working hours of 48.5 hours, a total of 28 nurses, with a total working hours of 776 hours, and a total of 30 midwives, with a total working hours of 388 hours. The optimization value obtained shows that the total number of doctors available per day is 1, the total number of nurses available per day is 16, and the total number of midwives available per day is 16. This research contributes to improving the operational efficiency of the Teja Community Health Center and the quality of health services. Optimal scheduling can help health workers work more efficiently and reduce fatigue.